Reform of Plan Termination in the Suspension of Debt Payment Obligations (PKPU) in Indonesia - Putra, Farih Romdoni (Yuridika, 2021)
Bankruptcy law exists to ensure justice for creditors and debtors. This research identifies areas of reform in Indonesian bankruptcy law to create justice for creditors and debtors. Specifically, this research focuses on the provisions of the termination of a plan achieved from the suspension of debt payment obligations (‘PKPU'). This research used a normative juridical research method with conceptual and comparative approaches. The author examined the bankruptcy law in Indonesia, evaluated several cases of plan termination in PKPU occurring in Indonesia, and later compared the rules in the bankruptcy laws applied in the United States of America (USA), the Netherlands and Singapore. The results of this study indicate that the provisions for plan termination in the bankruptcy law in Indonesia do not protect the debtors' interests. From the termination plan cases in Indonesia, confusion was found in the bankruptcy law, which did not provide legal certainty for both debtors and creditors. Comparing the bankruptcy laws in Indonesia, the USA, the Netherlands and Singapore shows that the Indonesian bankruptcy law needs reform to create flexibility to implement the plan. These findings are discussed further in this article.